2017
DOI: 10.1002/pen.24505
|View full text |Cite
|
Sign up to set email alerts
|

Effect of chemical modification on the thermal and rheological properties of polylactide

Abstract: Today PLA is one of the most important bioplastics on the market. A disadvantage of commercial polylactide is that it is not readily foamable, due to its low molecular weight, its low melt stability, and the lack of strain hardening effects. Therefore, commercially available polylactide has to be modified. In this study, the effects on properties by adding different modifiers were investigated. Adding of the modifiers and their chemical reaction were performed by means of reactive extrusion on a twin screw ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 19 publications
3
33
0
Order By: Relevance
“…The concentrations were selected based on pre-trials with 1.0 wt% for the chain extender and 0.2 wt m% for the peroxide. As described in a former study (25), the addition of the modifiers leads to an increase of molecular weight from 130,400 g/mol (neat PLA) to 200,600 g/mol (PLA+mEP) and 237,600 g/mol (PLA+PER), respectively. Also, topological changes of the polymer chains were described in our previous studies (25,30).…”
Section: Experimental 21 Materialssupporting
confidence: 58%
See 1 more Smart Citation
“…The concentrations were selected based on pre-trials with 1.0 wt% for the chain extender and 0.2 wt m% for the peroxide. As described in a former study (25), the addition of the modifiers leads to an increase of molecular weight from 130,400 g/mol (neat PLA) to 200,600 g/mol (PLA+mEP) and 237,600 g/mol (PLA+PER), respectively. Also, topological changes of the polymer chains were described in our previous studies (25,30).…”
Section: Experimental 21 Materialssupporting
confidence: 58%
“…The work of Södergård (24) showed that below 0.25 wt% branching is predominant while above 0.25 wt% significant crosslinking can be expected. In a former study (25) we could show, that thermal and rheological behavior significantly change by the addition of different chemical modifiers, like dicumyl peroxide.…”
Section: Introductionmentioning
confidence: 97%
“…PLA is a hard, transparent, biodegradable, and biocompatible polymer that could be derived from ring‐opening polymerization of lactide . Despite the high modulus, high strength, excellent processability, and low energy dependence, the application of this polymer in processes involving melt stretching (film extrusion, blow molding, foaming, and the like) have been limited due to disadvantages such as intrinsic brittleness, slow crystallization rate, low melt strength, narrow processing window, and low thermal stability . The low melt strength of PLA is due to the inherent degradation behavior of polyesters.…”
Section: Introductionmentioning
confidence: 99%
“…Typical modifiers that are used in combination with PLA can be distinguished by the occurring reaction into two groups: (i) functional group reactions and (ii) radical reactions and have been summarized in our previous work [4]. Additionally, the rheological as well as thermal behavior is influenced by the use of these modifiers [5]. The most common used modifier is the commercial additive Joncryl ® from BASF SE, which is a multi-functional epoxy based chain extender that reacts with the functional groups of PLA (i.e., carboxyl-and hydroxyl groups) during melt processing.…”
Section: Introductionmentioning
confidence: 99%